Short communication: heritability estimation of birth weight of swamp buffalo in Sabah, Malaysia - Soh, S. S.; Salisi, M. S.; Saad, M. Zamri; Goh, Y. M.; Yahaya, M. S.; Zulkafli, H. S. (Neoplasia Research, 2020)
Data on birth weight of Swamp buffalo calves that were born between 2015 and 2017 were collected and analyzed for this study. The objective was to estimate the effect of heritability and to evaluate the influence of environmental factors on the birth weight of swamp buffalo calves. The heritability was estimated using parent-offspring regression method while the environmental factors were measured using linear regression analysis. The average birth weight for swamp buffalo calves was 31.5 ± 5.33kg. It was significantly (p<0.05) affected by the age of dam and the year of birth but the body weight of the dam and the sex of calves did not significantly (p>0.05) influence the birth weight. The heritability of birth weight was estimated to be 0.29, which is low. Therefore, environmental and herd management factors seem to play a larger role in birth weight than genetics. The low estimated heritability obtained from this work indicates that improvement through selection may not be feasible.